2012
DOI: 10.1111/j.1442-200x.2012.03588.x
|View full text |Cite
|
Sign up to set email alerts
|

A case of meningoencephalitis associated with macrolide‐resistant Mycoplasma pneumoniae infection

Abstract: Mycoplasma pneumoniae, a common pathogen causing community-acquired pneumonia, is also known to cause meningoencephalitis in pediatric patients. We report herein a pediatric patient with meningoencephalitis and macrolide-resistant M. pneumoniae infection. We emphasize that macrolide-resistant M. pneumoniae must be taken into consideration in patients with encephalitis, along with consideration for using minocycline even in pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…They speculated that milder disease in their patients or a difference in blood sampling times could explain the apparent discrepancy with other studies. Life-threatening pneumonia and meningoencephalitis due to MRMP have also been reported (397,398).…”
Section: Macrolide Resistancementioning
confidence: 99%
“…They speculated that milder disease in their patients or a difference in blood sampling times could explain the apparent discrepancy with other studies. Life-threatening pneumonia and meningoencephalitis due to MRMP have also been reported (397,398).…”
Section: Macrolide Resistancementioning
confidence: 99%
“…Therefore, they suffer from less efficient protein synthesis and are deficient in growth ability (Narita, 2011b ). In fact, no excessive morbidity has been observed particularly ascribed to the drug resistance in the reported cases (Atkinson et al, 2011 ; Koga et al, 2012 ; Oishi et al, 2012 ). In addition to that, serum levels of IL-18, which represent disease activity of M. pneumoniae infection (Narita et al, 2000 ; Tanaka et al, 2002 ; Oishi et al, 2011 ; Miyashita et al, 2015a ), were rather lower in patients with pneumonia infected by the resistant strains than in patients infected by the sensitive strains (Matsuda et al, 2013 ).…”
Section: Possible Influence Of the Emergence Of Macrolide-resistant mentioning
confidence: 79%
“…Since 2000, when the first case of pneumonia due to macrolide-resistant M. pneumoniae was diagnosed in Japan (Okazaki et al, 2001 ), macrolide resistance has grown to be a significant problem in some countries, particularly in eastern Asia. A few cases of extrapulmonary manifestations due to macrolide-resistant M. pneumoniae have been reported (Atkinson et al, 2011 ; Koga et al, 2012 ; Oishi et al, 2012 ; Shen et al, 2013 ; Zhou et al, 2014 ). While the studies from China have reported that a substantial number of complications (most frequently liver and myocardial dysfunctions) occurred in patients infected by resistant strains (Shen et al, 2013 ; Zhou et al, 2014 ), no appreciable increase in the number of extrapulmonary manifestations has been observed in Japan in conjunction with a significant increase in the number of pneumonia patients infected by the resistant strains.…”
Section: Possible Influence Of the Emergence Of Macrolide-resistant mentioning
confidence: 99%
“…In 25% of M. pneumoniae infections, gastrointestinal symptoms (nausea, diarrhea, vomiting) have been described. Other clinical extrapulmonary symptomatology involving central nervous system, such as encephalitis and meningoencephalitis have been reported as well [23]. Complications affecting cardiac, hepatic, renal, skin and muscular systems (erythema multiforme) were reported less frequently [9].…”
Section: Mycoplasma Pneumoniaementioning
confidence: 99%